2002
DOI: 10.1192/pb.26.9.334
|View full text |Cite
|
Sign up to set email alerts
|

Intensive day programme treatment for severe anorexia nervosa – the Leicester experience

Abstract: Aims and MethodTo look at whether the opening of a day programme for the intensive care of people with severe anorexia nervosa in Leicester had the expected impact on admission rates, length of stay, cost of treatment and also simple measures of whether patients got better. Is this day programme an effective resource?ResultsSince the opening of the day programme, in-patient bed days and overall costs of treatment for local patients have been reduced, and the early results in terms of weight gain and readmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The idea of the treatment plan with different zones derives from the day‐care treatment for AN at Leicester General Hospital in Leicester, UK (Birchall et al . 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of the treatment plan with different zones derives from the day‐care treatment for AN at Leicester General Hospital in Leicester, UK (Birchall et al . 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The idea of the treatment plan with different zones derives from the day-care treatment for AN at Leicester General Hospital in Leicester, UK (Birchall et al 2002). The treatment model at the Stockholm Centre for Eating Disorders in Sweden has also inspired parts of the treatment programme.…”
Section: Treatment Modelmentioning
confidence: 99%
“…They have also demonstrated comparable or superior outcomes when compared to inpatient (IP) and outpatient (OP) treatment (Kong, 2005;Zeeck, Herzog, & Hartmann, 2004 concluded that DP programmes are able to achieve cognitive and behavioural changes in patients with eating disorders across treatment (Zipfel et al, 2002). Significant reductions in bingeing and purging behaviour in bulimia nervosa (BN) has consistently been reported (Fittig, Jacobi, Backmund, Gerlinghoff, & Wittchen, 2008;Gerlinghoff et al, 1998;Peake, Limbert, & Whitehead, 2005;Piran, Langdon, Kaplan, & Garfinkel, 1989a;Thornton, Beumont, & Touyz, 2002), as well as weight gain for patients with anorexia nervosa (AN) (Birchall, Palmer, Waine, Gadsby, & Gatward, 2002;Piran, Langdon, Kaplan, & Garfinkel, 1989a;Fittig et al, 2008) and in underweight BN patients (Guarda & Heinberg, 1999;Peake et al, 2005). Improvements in disturbed cognitions towards eating, weight and shape have also been found across DP treatment.…”
Section: Introductionmentioning
confidence: 95%
“…Alongside hospital programs, a number of specialized day patient treatments for AN have been developed for adults and older adolescent patients (Birchell, Palmer, Waite, Gadsby, & Gatward, 2002;Gerlinghoff, Backmund, & Franzen, 1998;Robinson, 2003;Zipfel et al, 2000). Usually, day programs run 4 to 7 days per week and consist of supervised meals, a variety of therapeutic groups and sometimes concurrent individual therapy (Olmsted, 2002).…”
Section: Inpatient Program Care and Residential Carementioning
confidence: 99%